2019
DOI: 10.1002/hbm.24911
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring of contralateral gray matter volume associated with cognition in patients with unilateral temporal lobe glioma before and after surgery

Abstract: Glioma can cause variable alterations to the structure and function of the brain. However, there is a paucity of studies on the gray matter (GM) volume alterations in the brain region opposite the temporal glioma before and after surgery. Therefore, the present study was initiated to investigate the alternation in contralateral homotopic GM volume in patients with unilateral temporal lobe glioma and further, assess the relationship between GM volume alternations with cognition. Eight left temporal lobe glioma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 43 publications
(74 reference statements)
8
24
0
Order By: Relevance
“…Since, the glioma is commonly thought to disrupt functional networks and decrease FC 25 , 32 , 33 . Hence, the increasing FC implied that network reorganization occurred similar to what other studies have shown 3 , 10 , 19 , 20 . No significant sensorimotor and abnormal mental status were found in our patients.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Since, the glioma is commonly thought to disrupt functional networks and decrease FC 25 , 32 , 33 . Hence, the increasing FC implied that network reorganization occurred similar to what other studies have shown 3 , 10 , 19 , 20 . No significant sensorimotor and abnormal mental status were found in our patients.…”
Section: Discussionsupporting
confidence: 82%
“…In this study, we investigated the alterations of functional networks in patients with insular DLGGs. Our findings indicate that insular gliomas in different hemispheres can induce different alterations of functional networks, and these alterations may be related to functional compensation 10 .…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…These inherent characteristics indicate that IDHwt-A glioma has higher invasiveness and greater tumor momentum than IDHm glioma. Furthermore, highly invasive IDHwt-A glioma not only damages the brain network more quickly but also has a negative effect on neuroplasticity, which ultimately leads to worse NCF performance (24)(25)(26)(27)(28). As our data suggest, patients who present with more rapid and extensive NCF decline may be likely to harbor aggressive characteristics, such as genetic alteration of IDHwt.…”
Section: Discussionmentioning
confidence: 76%